2020
DOI: 10.1177/0379572119895860
|View full text |Cite
|
Sign up to set email alerts
|

Are Low-Income Consumers Willing to Pay for Fortification of a Commercially Produced Yogurt in Bangladesh

Abstract: Background: There is an active debate over the potential for market-based strategies to address micronutrient deficiencies in low- and middle-income countries. However, there are questions over the viability of market-based strategies, reflecting limited evidence on the value that low-income households attach to the nutritional attributes of processed foods. Objective: The objective of this article is to investigate the willingness to pay of primary food purchasers in low-income households in rural Bangladesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This is, for instance, observable in the case of Danone (a MNC based in France) and Grameen Bank (a NGO based in Bangladesh), which collaborated in an initiative to produce Shokti Doi (a yogurt) for malnourished poor children in Bangladesh. While this yogurt was a good product, the problem was that it was a luxury product for poor children (Agnew, Henson, & Cao, 2020). When this yogurt was first produced, there was no feasible way to encourage the families of the targeted children to buy it (Bapat, 2011).…”
Section: Potentials Of Entrepreneurship Literature In Relation To Ms ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is, for instance, observable in the case of Danone (a MNC based in France) and Grameen Bank (a NGO based in Bangladesh), which collaborated in an initiative to produce Shokti Doi (a yogurt) for malnourished poor children in Bangladesh. While this yogurt was a good product, the problem was that it was a luxury product for poor children (Agnew, Henson, & Cao, 2020). When this yogurt was first produced, there was no feasible way to encourage the families of the targeted children to buy it (Bapat, 2011).…”
Section: Potentials Of Entrepreneurship Literature In Relation To Ms ...mentioning
confidence: 99%
“…When this yogurt was first produced, there was no feasible way to encourage the families of the targeted children to buy it (Bapat, 2011). In fact, many children in rural Bangladesh do not even know what yogurt is and have no knowledge of its nutritional content or why it is important for their health (Agnew et al, 2020).…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Hussein et al [89] respectively, for foods fortified in carotenoids, folate, and fortified maize [90][91][92]. A recently published study by Agnew et al, [93] reported that 96% of the study population in Bangladesh were willing to pay the market price of 10 Bangladeshi takas (BDT) or the US $0.14 for a pack of 60g micronutrient fortified yogurt. The yogurt targeted children aged 3 to 12 years.…”
mentioning
confidence: 99%